Advances in Applied Economics, Business and Development International Symposium, ISAEBD 2011, Dalian, China, August 6-7, 2011, Proceedings, Part II - Zhou, Qingyuan (Communications in Computer and Information Science, 2011)
This four-volume-set (CCIS 208, 209, 210, 211) constitutes the refereed proceedings of the International Symposium on Applied Economics, Business and Development, ISAEBD 2011, held in Dalian, China, in August 2011. The papers address issues related to Applied Economics, Business and Development and cover various research areas including Economics, Management, Education and its Applications.